Guttulapsyche mayaensis, gen. et sp. nov., a Psychidae from Mexico with unusual larval ethology (Insecta: Lepidoptera: Typhoniinae) - Sobczyk, Thomas (Zootaxa, 2021)
A new genus and species, Guttulapsyche mayaensis gen. et sp. nov., of Psychidae are described from Mexico. The new taxon shares some characters with Arrhenophaninae and several others with Typhoniinae. Together with Antillonatus sessilis Núñez & Davis, 2016 it is already the second Neotropic species with a complex of characteristics that deviates from the previous understanding of the two subfamilies. The morphology of adults, larva, and pupa is described and illustrated. The larval cases are attached at the distal end, a behaviour that is unique among all known Psychidae. Information on distribution and habitat as well as some ecological data are provided.